Eradication of Land Mafia in Indonesia by the Ministry of Agrarian Affairs and Spatial Planning of the Republic of Indonesia or the National Land Agency - Amrullah Amrullah; Herman Bakir (PT Publikasiku Academic Solution, 2024)
The land mafia in Indonesia is a complex phenomenon that harms society and has the potential to disrupt social stability. This research aims to analyze the practices of land mafia that occur in Indonesia and evaluate the eradication efforts by the Ministry of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN). Land mafia practices include certificate forgery, illegal land occupation, and document manipulation that threaten the ownership rights of the community. This research uses normative legal research methods, which involve the process of finding legal rules, principles, and legal doctrines to answer the legal issues at hand. Furthermore, this research also examines the policies and strategic steps taken by the ATR/BPN in combating the land mafia, including the establishment of the Anti-Land Mafia Task Force and the strengthening of land regulations. The results indicate that despite various eradication efforts, challenges in law enforcement and inter-agency coordination remain obstacles. Therefore, better synergy between the government, society, and the private sector is necessary to create a transparent and accountable land system. This research is expected to contribute to the development of more effective policies in eradicating the land mafia in Indonesia and reinforcing legal protection for the community.